2021
DOI: 10.1002/jso.26776
|View full text |Cite
|
Sign up to set email alerts
|

Impact of preoperative sarcopenia in patients undergoing sacral tumor resection

Abstract: Introduction Sacral tumor resection is known for a high rate of complications. Sarcopenia has been found to be associated with wound complications; however, there is a paucity of data examining the impact of sarcopenia on the outcome of sacral tumor resection. Methods Forty‐eight patients (31 primary sarcomas, 17 locally recurrent carcinomas) undergoing sacrectomy were reviewed. Central sarcopenia was assessed by measuring the psoas:lumbar vertebra index (PLVI), with the 50th percentile (0.97) used to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In addition, the prevalence of sarcopenia is also affected by racial and regional differences. Compared with studies based on the EWGSOP consensus algorithm, studies that use muscle mass as the sole diagnostic criterion have a higher prevalence of sarcopenia (Batsis et al, 2013;Brinkmann et al, 2022).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the prevalence of sarcopenia is also affected by racial and regional differences. Compared with studies based on the EWGSOP consensus algorithm, studies that use muscle mass as the sole diagnostic criterion have a higher prevalence of sarcopenia (Batsis et al, 2013;Brinkmann et al, 2022).…”
Section: Discussionmentioning
confidence: 97%
“…A few studies have identified risk factors for poorer oncologic and surgical outcomes in pelvic tumors. These include a venous tumor thrombus, a margin of <2 mm, complete acetabular resection compared with transacetabular resection, and sarcopenia 1,3,7,8 .…”
Section: Pelvis and Spinementioning
confidence: 99%
“…A few studies have identified risk factors for poorer oncologic and surgical outcomes in pelvic tumors. These include a venous tumor thrombus, a margin of <2 mm, complete acetabular resection compared with transacetabular resection, and sarcopenia 1,3,7,8 .The National Cancer Institute's Surveillance, Epidemiology, and End Results (SEER) database, the American College of Surgeons (ACS) National Cancer Database, and the California Cancer Registry were queried by several authors who concluded that radiation therapy is the most common local modality used in the United States for Ewing sarcoma of the sacrum or pelvis and has similar efficacy to surgical resection with or without radiation therapy; that 5-year disease-specific survival in patients with mobile vertebral column sarcomas was 56%, with worse survival for osteosarcoma; and that patients with malignancies of the mobile spine with public insurance are vulnerable to worse outcomes, even if they receive standard treatment 6,9,11 .Disclosure: The Disclosure of Potential Conflicts of Interest forms are provided with the online version of the article (http://links.lww.com/JBJS/H270).…”
mentioning
confidence: 99%